2018
DOI: 10.1039/c8py00722e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of molecular structure and fluorination on the properties of pyrene-benzothiadiazole-based conjugated polymers for visible-light-driven hydrogen evolution

Abstract: The linear non-fluorinated polymer L-PyBT exhibited an impressive hydrogen evolution rate up to 83.7 μmol h−1 under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 57 publications
1
33
1
Order By: Relevance
“…[29] Similar studies also reflect this, whereby the measured surface area showed no relationship to photocatalytic activity. [33,[103][104][105][106][107] Figure 5. Cryo-transmission electron microscopy images of NP HEPs formed from a 3:7 blend of the polymer PTB7-Th (12) and the nonfullerene acceptor EH-IDTBR (13) with 10 wt% photodeposited Pt cocatalyst after 20 h H 2 evolution.…”
Section: Conjugated Network Polymers For Hydrogen Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Similar studies also reflect this, whereby the measured surface area showed no relationship to photocatalytic activity. [33,[103][104][105][106][107] Figure 5. Cryo-transmission electron microscopy images of NP HEPs formed from a 3:7 blend of the polymer PTB7-Th (12) and the nonfullerene acceptor EH-IDTBR (13) with 10 wt% photodeposited Pt cocatalyst after 20 h H 2 evolution.…”
Section: Conjugated Network Polymers For Hydrogen Evolutionmentioning
confidence: 99%
“…[108,109,111] This branching can have the effect of reducing planarity and decreasing the extent of conjugation, hence widening the optical bandgap, leading to poorer utilization of visible light and diminished photocatalytic activity. The reduced planarity in polymer backbones caused by high degrees of torsion also impedes intramolecular charge transport along the backbone, [104,109,111] given that conjugated network polymers with greater adjacent unit planarity have improved intramolecular charge transport. [112,113] Taken together, this could explain how the advantages of porosity can be outweighed by these other factors, and contorted porous network polymers are often less photocatalytically active than their low or nonporous linear polymer equivalents.…”
Section: Conjugated Network Polymers For Hydrogen Evolutionmentioning
confidence: 99%
“…Recently, Wang et al. also developed novel CPs combining pyrene and BT units with either linear or porous networks for hydrogen production and investigated the effects of fluorine substitution on the polymer backbone . Surprisingly, the linear non‐fluorinated polymer (L−PyBT) showed an excellent HER of 1,674 μmol h −1 g −1 with an AQY of 10.3 % at 420 nm under visible light.…”
Section: Conjugated Linear Polymers Containing a Donor‐acceptor (D‐a)mentioning
confidence: 99%
“…1D linear polymers show enhanced conductive performance and higher charge‐transmission ability along the 1D polymer backbone than 3D polymers, and thus exhibit higher photocatalytic activity. The introduction of functional groups (e.g., O=S=O, NH 2 , F, and CN) could modify the surface chemistry and the energy band structure of organic polymer photocatalysts, which significantly affect the photocatalytic performance. Considering the diverse structural variations, flexible molecular design, and wide number of organic building blocks, further improvement in photocatalytic activity for hydrogen generation could be expected by porous organic polymer photocatalysts.…”
Section: Introductionmentioning
confidence: 99%